CORR Insights™: Intramedullary Nails Result in More Reoperations Than Sliding Hip Screws in Two-part Intertrochanteric Fractures - Dougherty, Paul J. (Springer-Verlag, 2013)
This CORR Insights™ is a commentary on the article “Intramedullary Nails Result in More Reoperations Than Sliding Hip Screws in Two-part Intertrochanteric Fractures” by Matre et al. available at DOI-10.1007/s11999-012-2728-2.